A Place of Belonging: Including Individuals With Significant Disabilities in Faith Communities. Issue 1 (February 2022) - Carter, Erik W.
Faith is central to the flourishing of so many children and adults with significant disabilities and their families. For congregations striving to be a place of inclusion and belonging for their entire community, the theological call to welcome people with disabilities can introduce a host of questions: What does it mean to be a community marked by belonging? What strategies and supports should we adopt to include people well? How can others assist us in this essential endeavor? This article presents a framework for reflecting on the practices and commitments of local congregations that contribute to belonging within a community of faith.